NAVIGATING MODERN CHALLENGES IN ISLAMIC RELIGIOUS EDUCATION IN URBAN MUSLIM COMMUNITIES - Taufikin, Taufikin; Nurhayati, Sri; Muzakki, Ahmad; Adeoye, Moses Adeleke (AKADEMIKA: Jurnal Pemikiran Islam, 2025)
This study examines how Islamic schools in urbanized areas of East Kutai, a district in East Kalimantan, Indonesia, navigate pedagogical adaptation, maintain religious authenticity, and address the impact of student diversity. While East Kutai is geographically a district, its urbanized centers, particularly in towns like Sangatta, have seen rapid development, leading to an increasingly diverse student population and a blend of traditional and modern educational approaches. Using a mixed-methods approach, the study collected survey data from 309 students and conducted interviews with 36 teachers, parents, and students across four Islamic schools in the region. The findings reveal that blended learning models enhance engagement but require contextual adaptation to preserve religious depth. Privately funded schools demonstrate greater adaptability, while government-funded madrasahs face resource limitations. Additionally, cultural diversity enriches classroom discussions but complicates standardized learning. The study highlights the need for hybrid pedagogical strategies integrating digital tools without compromising theological integrity. Policymakers must address funding disparities and support teacher training to ensure inclusive, high-quality IRE. This research contributes to the discourse on religious education by proposing a contextualized digital adaptation model, offering practical recommendations for sustaining Islamic educational identity in urbanized settings.